Functional tunability of biological circuits from additional toggle switches. Issue 5 (1st October 2013) - Shi, Changhong; Zhou, Tianshou; Yuan, Zhanjiang
Abstract : In many complex regulatory networks with interlinked feedback loops, the simple core circuits are sufficient to achieve the specific biological functions of the whole networks, naturally raising a question: what is the role of the additional feedback loops. By investigating the effect of an additional toggle switch on the auto‐activation circuit responsible for competent switch in Bacillus subtilits and on the activator–repressor circuit responsible for cell cycle in Xenopus embryonic, the authors show that the additional toggle switch can elaborate the dynamical behaviour of both circuits. Specifically, the additional toggle switch in B. subtilits does not significantly affect the saturation level of the competent state but can tune the activation threshold (i.e. the minimal stimulus required to switch the system from the non‐competent state to the competent state). For the activator–repressor circuit in X. embryonic cell cycle, the additional toggle switch can tune the oscillation frequency but does not change the oscillation amplitude. The proposed detailed results not only provide guidelines to the engineering of synthetic genetic circuits, but also imply a significant fact that additional toggle switches in a complex network are not really redundant but play a role of tuning network functions.